Comparison of Biomarkers of Neonatal Sepsis: Pro- Calcitonin Vs C-Reactive Protein - Dr. Angadi Wasim Akram; Dr. Altaf Naseem (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Procalcitonin in neonatal sepsis (NS) has high sensitivity compared to C-reactive protein (CRP), but its specificity is not yet clearly defined. Objectives: Evaluation of Procalcitonin as an early marker, assessing its diagnostic utility in early-onset NS was the primary and comparing the levels of Procalcitonin with CRP was secondary objective. Method: In this observational, prospective study, neonates meeting the selection criteria were included and grouped into three, according to clinical symptoms of sepsis and blood culture. Results: Blood samples from 75 babies (male = 61.0%) were analysed; 63.0% and 37.0% were of gestational age (GA) ≥ 37 and < 37 and weeks, respectively. Birth-weight< 2.5 kg and >2.5 Kg was noted in 52.0% and 48.0%, respectively. Meconium stained liquor (n=34), premature rupture of membranes (n=19) and prolonged labour/instrumental delivery (n=13) were major maternal risk factors.General (45.33%), respiratory (25.33%), gastrointestinal (17.33%), cardiovascular (6.66%)symptoms were common presentation; forty one (55.0%) were negative for procalcitonin and 34 (45.0%) were positive; 61 (81.0%) tested negative for CRP, only 14 (19.0%) were positive with levels >10mg/mL. Procalcitonin positivity was statistically significant (<0.05) for males, term babies and with normal birth weight favouring procalcitonin. of seven positive blood culture, coagulase positive staphylococci (n= 03), Klebsiella(n= 02), E. coli (n=01), Pseudomonas (n=01) were isolated. On correlation with blood culture, Procalcitonin showed better sensitivity and negative predictive value. Conclusion: Procalcitoninis a better early marker than CRP in early onset NS. It hasbetter positivity for male, term and normal birth weight babies.